PENERAPAN MODEL PEMBELAJARAN KARTU ARISAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN TATA NAMA SENYAWA DAN PERSAMAAN REAKSI SEDERHANA DI KELAS X SMA TRI BHAKTI PEKANBARU - Camelia Situmorang Camelia Situmorang; Maria Erna Maria Erna; Betty Holiwarni Betty Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRAK :Research about aplication of learning Model with Lottery Card has been conducted to improvement of student’s learning achievement at compounds nomenclature and chemical reaction equation subject in SMA Tri Bhakti Pekanbaru. This research was quasi experimental with pretest-posttest design. The sample consist of two classes,class X sain 2 as the experiment class and class X Sain 1 as the control that randomly selected after normality and homogenity test. Model learning with lottery card applied in X Sains 2. Data Analysis of data used t-test formula. Result of data preparation obtained tcount>ttable is 2,79 > 1,67 It means the application of learning model with lottery card can improve student achievement on the topic compounds nomenclature and chemical reaction equation at class X SMA Tri Bhakti Pekanbaru is 11,8%.Keyword: Learning model With lottery Card, study achievement, compounds nomenclature and chemical reaction equation